Determinants of Trade Policy Responses to the 2008 Financial Crisis - Gawande, Kishore; Hoekman, Bernard; Cui, Yue (2012)
The collapse in trade and contraction of output that occurred during 2008-09 was comparable to, and in many countries more severe than, the Great Depression of 1930, but did not give rise to the rampant protectionism that followed the Great Crash. Theory suggests several hypotheses for why it was not in the interest of many firms to lobby for protection, including much greater macroeconomic "policy space" today, the rise of intra-industry trade (specialization in specific varieties), and the fragmentation of production across global value chains ("vertical" specialization and the associated growth of trade in intermediates). Institutions may also have played a role in limiting the extent of protectionist responses. World Trade Organization disciplines raise the cost of using trade policies for member countries and have proved to be a stable foundation for the open multilateral trading system that has been built over the last fifty years. This paper empirically examines the power of these and other theories to explain the observed pattern of trade policy responses to the 2008 crisis, using trade and protection data for seven large emerging market countries that have a history of active use of trade policy. Vertical specialization (global fragmentation) is found to be the most powerful economic factor determining trade policy responses.